Pengaruh Asimetri Informasi, Karakter Personal, Reputasi, Trust in Superior dan Mutual Monitoring terhadap Budgetary Slack - Ietje Nazaruddin; Nurul Harsanti (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2021)
This study aims to determine the effect of information asymmetry, personal character, reputation, trust in superiority and mutual monitoring of budgetary slack. The sample used was individuals working in the SKPD consisting of 1 City and 4 Regencies in the Special Region of Yogyakarta (DIY). This research uses purposive sampling. A total of 200 questionnaires were distributed and only 105 questionnaires could be processed. The process of data analysis in this study uses multiple regression analysis with the application of SPSS. The results showed that the information asymmetry variable had a positive and significant effect on budgetary slack, personal character, reputation and trust in superior had a negative and significant effect on budgetary slack. Keywords: Asymmetry Information, Personal Character, Reputation, Trust In Superior, Mutual Monitoring, Budgetary Slack